Effect of temperature and methane on the electrical conductivity of SnO2 (100-x) Pd(x) semiconductor gas sensor systems - Dennis, J. O.; Mohd. Mustamam Abd. Karim; Md. Rahim Sahar, 1957-; Mohamad Khairi Saidin; Persidangan Serantau Sains Keadaan Pepejal (15th. : 1998 : Selangor) (Skudai : Universiti Teknologi Malaysia, 1999)
50